Exil temporel chez les migrants de retour en Géorgie post-soviétique - Maroussia Ferry (Temporalités, 2015)
For some returning migrants in post-Soviet Georgia, their exile is made more painful by a brutal historic break with "time past", thus revealing the perception of another form of exile, which is of a social and temporal kind. This temporal exile shapes an original perception of time consisting of various disruptions told by migrants who mobilize various narrative tools to restore fragmented individual pathways in socially shared time. The narratives stage the inaugural pattern of the Fall and establish the link between migrating and the fear of national fragmentation. They also reveal social polarities that we understand as differentiated temporal perceptions. The disruption-continuity dialectic differs depending on the social position of the respondents. According to whether one was able to see the end of the post-Soviet "difficult years" or not, these will be considered as a completed transition or as a never-ending crisis, out of phase with the rapid political temporality of Mikheil Saakashvili’s government.Thus, by combining the precarious rhythms of mobility, the temporal apprehension of migrants here can be grasped at the intersection of both historical perspectives and the perspective of migration and biographical trajectories.